The History of Lithuanian Sociology (I) - Kraniauskas, Liutauras (Sociologija. Mintis ir veiksmas, 2000)
The aim of the article is to analyze the notion of the history of national sociology and to discuss the methodological problems that the notion suggests. The author takes his point of departure by distinguishing two traditions in the historiography of the history of sociology: the history of ideas and the analytical tradition. The difference of historiographic traditions is the difference of function of the history of sociology: while the history of ideas is connected with the development of the identity of a discipline, the analytical is concerned with the sociological self-understanding of the discipline. The author of the article attempts to define an analytical methodology to analyze the history of national sociology.